Amyloid Beta Peptide Slows Down Sensory-Induced Hippocampal Oscillations. (29th April 2012) - Peña-Ortega, Fernando; Bernal-Pedraza, Ramón
Abstract : Alzheimer's disease (AD) progresses with a deterioration of hippocampal function that is likely induced by amyloid beta (A β ) oligomers. Hippocampal function is strongly dependent on theta rhythm, and disruptions in this rhythm have been related to the reduction of cognitive performance in AD. Accordingly, both AD patients and AD-transgenic mice show an increase in theta rhythm at rest but a reduction in cognitive-induced theta rhythm. We have previously found that monomers of the short sequence of A β (peptide 25–35) reduce sensory-induced theta oscillations. However, considering on the one hand that different A β sequences differentially affect hippocampal oscillations and on the other hand that A β oligomers seem to be responsible for the cognitive decline observed in AD, here we aimed to explore the effect of A β oligomers on sensory-induced theta rhythm. Our results show that intracisternal injection of A β 1–42 oligomers, which has no significant effect on spontaneous hippocampal activity, disrupts the induction of theta rhythm upon sensory stimulation. Instead of increasing the power in the theta band, the hippocampus of A β -treated animals responds to sensory stimulation (tail pinch) with an increase in lower frequencies. These findings demonstrate that A β alters induced theta rhythm, providing an in vivo model to test for therapeutic approaches to overcome A β -induced hippocampal and cognitive dysfunctions.